The relationship between selected psychological parameters and performance among swimmers and divers - Stallmann, R.; Vikander, N.; Freim, N. P. (Biomechanics and Medicine in Swimming. Swimming Science VI, 1992)
One hundred and forty two swimmers and divers were ranked according to performance. Three self-report instruments from the Sport Psychology Consultation System (Rushall, 1985) were also administered to the subjects. Scores from these instruments were correlated with performance. In addition, for each instrument, the subjects were grouped in various ways (e.g. male vs female) and the scores were tested for group differences. The results showed low but significant correlations between performance and achievement motivation. No significant correlations were found between performance and selfcontrol or locus of control. Significant group differences were found, however, between elites and sub-elites as well as between males and females, especially for achievement motivation.